2018
DOI: 10.5194/hess-22-1095-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Weather Research and Forecasting (WRF) model for simulation of extreme rainfall events in the upper Ganga Basin

Abstract: Abstract. Reliable estimates of extreme rainfall events are necessary for an accurate prediction of floods. Most of the global rainfall products are available at a coarse resolution, rendering them less desirable for extreme rainfall analysis. Therefore, regional mesoscale models such as the advanced research version of the Weather Research and Forecasting (WRF) model are often used to provide rainfall estimates at fine grid spacing. Modelling heavy rainfall events is an enduring challenge, as such events depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 88 publications
(120 reference statements)
1
56
0
1
Order By: Relevance
“…The 72 h real-time forecast data of the WRF model underestimated the rainfall for all the events, which led to the underestimation of the real-time flood forecast in the studied area. The underestimation of the WRF model has also been reported in previous studies [28], which is in agreement with our current study. The application of the bias correction methods resulted in a more accurate rainfall forecast.…”
Section: Discussionsupporting
confidence: 94%
“…The 72 h real-time forecast data of the WRF model underestimated the rainfall for all the events, which led to the underestimation of the real-time flood forecast in the studied area. The underestimation of the WRF model has also been reported in previous studies [28], which is in agreement with our current study. The application of the bias correction methods resulted in a more accurate rainfall forecast.…”
Section: Discussionsupporting
confidence: 94%
“…The WRF model, a popular numerical weather prediction system, was used and applied in both atmospheric research and forecast. It has been an extensively used model recently, especially in heavy rainfall research over the Indian region (Fadnavis et al ., ; Chawla et al ., ; Karki et al ., ; Madhulatha and Rajeevan, ; Reshmi et al ., ). A recent study by Chawla et al .…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Chawla et al . () found that the WRF‐simulated rainfall exhibit less bias compared with national centers for environmental prediction final (NCEP‐FNL) reanalysis data. The WRF model is a highly customizable model with several radiation, planetary boundary layer (PBL), cloud microphysics and convection physics options.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations